Investigação sobre a difusividade térmica na junção Metal/cerâmica AISI 304L/YBa2Cu3O7−δ - Oliveira, Patrício Santana de (2017)
Superconducting ceramic materials are generally hard and brittle, have low tensile and impact strength and low heat diffusion capacity. This imposes limitations for technological applications when superconducting ceramics are subjected to electrical and thermal stresses. Thus, an alternative is to combine the properties of superconducting ceramics with the properties of metals. With this objective in mind, in this dissertation the deposition of superconducting ceramic YBa2Cu3O7-δ in stainless steel AISI 304 L followed by thermal treatment was investigated. The thermal diffusivity measurements were performed with a carbon dioxide laser with Gaussian space profile, wavelength 10 μ!, intensity 10√2 # / !2 and diameter equal to 1 !!. In order to make comparisons, the thermal diffusivity measurement in AISI 304 L stainless steel plate, as received, presented value similar to the value supplied by the manufacturer. Using plates of AISI 304 L, several substrates with dimensions of 70 x 10 x 3mm were manufactured. Posteriorly, these substrates were milled, producing rectangular channels of 2 mm wide by 1.25 mm deep. The channels were filled with YBaCuO electroceramics. This assembly was baked for 15 min at a temperature of 1040°C, being removed and cooled in the air, generating samples of the junction. These junction samples were characterized by XRD, AC magnetic susceptibility and scanning electron microscopy. Finally, the thermal diffusivity measurements were performed by the flash method at the junction. The thermal diffusivity of the metal/ceramic junction presented values close to those theoretically estimated, considering the hypothesis of additivity without interference between the compounds. However, these conclusions are partial, which reinforces the need for further studies on the thermal diffusivity of this metal /ceramic junction.